Bootstrapping safe IVIS development with an affordable testing suite - Mandarino, Leonel (2022)
In-vehicle information systems (IVIS) represent a growing industry. IVIS were originally built and deployed by car manufacturers, which ensured that they complied with the safety regulations of the car industry. Nowadays, IVIS enter the vehicle in the driver’s and passenger’s phones. These “nomadic IVIS”, which sometimes interact with the car’s entertainment system, can escape important safety checks. Any software developer, without training in vehicle safety, can build and distribute IVIS. This reality calls for tools and methods that help software developers conceive safe applications. This article proposes an affordable and reliable testing suite that provides support to developers of nomadic IVIS. The suite takes the form of a simulation and data collection environment, oriented to the rapid prototyping of IVIS. It considers security requirements while maintaining a low technological and economic threshold, to provide easy access to developers compared to expensive physical environments with real vehicles.